2023
DOI: 10.3389/fcimb.2023.1052020
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between alveolar macrophages and epithelial cells during Mycoplasma pneumoniae infection

Abstract: Mycoplasma pneumoniae, as one of the most common pathogens, usually causes upper respiratory tract infections and pneumonia in humans and animals. It accounts for 10% to 40% of community-acquired pneumonia in children. The alveolar epithelial cells (AECs) are the first barrier against pathogen infections, triggering innate immune responses by recruiting and activating immune cells when pathogens invade into the lung. Alveolar macrophages (AMs) are the most plentiful innate immune cells in the lung, and are the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 138 publications
0
5
0
Order By: Relevance
“…Previous studies have reported that bacteria-released pEVs can inherit pathogen-associated molecular patterns of bacteria, and can be effectively recognized and internalized by host cells via endocytosis [ 11 , 46 ]. Alveolar epithelial cells, the first line of defense against pathogens, play a critical role in preventing bacteria from entering the bloodstream [ 47 , 48 ]. We thus wondered whether S. pneumoniae -secreted pEVs could be internalized into alveolar epithelial cells.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have reported that bacteria-released pEVs can inherit pathogen-associated molecular patterns of bacteria, and can be effectively recognized and internalized by host cells via endocytosis [ 11 , 46 ]. Alveolar epithelial cells, the first line of defense against pathogens, play a critical role in preventing bacteria from entering the bloodstream [ 47 , 48 ]. We thus wondered whether S. pneumoniae -secreted pEVs could be internalized into alveolar epithelial cells.…”
Section: Resultsmentioning
confidence: 99%
“…15 Studies have shown that the membrane lipoprotein of MP binds to Tolllike receptors (TLRs) on alveolar macrophages (AM), which can activate the nuclear factor-κB(NF-κB) signaling pathway, leading to the release of pro-inflammatory cytokines such as interleukin-8 (IL-8), tumor necrosis factor-α (TNF-α), interferon (IFN), and granulocyte-macrophage colony-stimulating factor (GM-CSF), thereby promoting neutrophils aggregation and pathogens phagocytosis. 16,17 As the severity of MP infection escalates, there is a concurrent increase in the levels of IL-8 and TNF-α in the patients' serum. 16,18 Lee et al have also confirmed that after MP adheres to alveolar epithelial cells (AECs), ACEs can produce a significant amount of extracellular vesicles rich in miRNA.…”
Section: Discussionmentioning
confidence: 99%
“…16,17 As the severity of MP infection escalates, there is a concurrent increase in the levels of IL-8 and TNF-α in the patients' serum. 16,18 Lee et al have also confirmed that after MP adheres to alveolar epithelial cells (AECs), ACEs can produce a significant amount of extracellular vesicles rich in miRNA. These miRNA-enriched extracellular vesicles are actively delivered to alveolar macrophages (AM), promoting neutrophil recruitment and inflammasome activation, leading to excessive inflammatory response and subsequent impairment of the host's immune function.…”
Section: Discussionmentioning
confidence: 99%
“…are mainly realized by the supramolecular non‐covalent and covalent synergistic interactions between biomolecules at the interface because of the relatively low interaction energy and reversibility of supramolecular non‐covalent bonding imbedded into stable mechanical polymer covalent frame. [ 2,3,12,15–17 ] Supramolecular non‐covalent interactions have a large role in biological growth and exercise of function. For example, DNA base complementary pairings are held together mainly by hydrogen bonding interactions.…”
Section: Introductionmentioning
confidence: 99%